(untitled) (Annals of Medical Research, 2021)
Aim: To invastigate the inflammatory process and hormone parameters as a result of underlying cause of unexplained infertility (UI)Metarial and Methods: In total 153 patients with UI who underwent to intracytoplasmic sperm injection (ICSI) were included in the study. The blood hormones levels were obtained on the 2nd or 3rd day of the menstruation. Other blood count examinations were taken on the day of HCG administration. Relationship regarding embryo grade was also investigated.Results: Of those 153 patients, only 42 of them got pregnant. Mean maternal age was 29.08±3.5 and mean duration of the infertility was 8.19±3.1 years, respectively. There was no statistically significant difference between pregnancy rate, embriyo grade, and FSH, progesterone, fT3, fT4, TSH levels (p>0.05). Also no significant difference was found between pregnancy rate, embriyo grade and hemoglobin, hemotocrit, platelet, mean platelet volume, neutrophil, lymphocyte counts, neutrophil lymphocyte ratio and platelet lymphocyte ratio (PLR) (p>0.05). However, a significant difference was found between embriyo grade and estradiol values (p0.05). There was a negative correlation between hematocrit values and the oosit number collected with the number of embryos (p0.05). PLR was found to be 110.9 (63.6 - 313.2) in pregnant women and 110.5 (51.8 - 390) in nonpregnant patients and the correlation between the PRL measured on HCG day and pregnancy rate.was significant (p=0.002). LH median values measured on HCG day were significantly lower in pregnant group (p0.001). Conclusion: We found that inflammation does not affect on IVF result and estradiol levels significantly effects on embriyo quality. Also there was an inverse correlation between hematocrit levels and the number of oocyte- and number of embryos.Keywords: Infertility; blood cell count; inflammation; estrogen.